Realisasi Program Pengelolaan dan Pemantauan Lingkungan (UKL-UPL) di Kota Sorong - Victorina Tutiana Kambuaya; Anton S. Sinery; Max J. Tokede (Cassowary, 2020)
Environmentally sound development is a development effort undertaken with due regard to environmental aspects. UKL-UPL is an instrument that is expected to be a deterrent of environmental pollution and damage, which in its application UKL-UPL is one of the prerequisites to obtain Environmental Permit. The aim of the research is to know the realization of environmental management and monitoring activities as contained in the UKL-UPL document of environmental permit holders in Sorong City area and the factors that influence the successful implementation of environmental management and monitoring activities. Objects observed in this study were environmental permit holders who implement environmental management and monitoring (UKL-UPL) program in Sorong City. The environmental permit holders are three (3) types of business and or activity consisting of andesite mining activities by PT. Lintas Artha Lestari, then shopping service activities by Mall Ramayana and Activity of power plant by PLTD Klasaman. The method used in this research was descriptive method with observation and interview technique. The results of research in general realization of each business owner and or activity in realizing environmental management program was relatively different both in terms of the number and completion of the completion of activities. PT. Lintas Artha Lestari successful UKL realization UPL quite successful. Factors that contribute to the realization are Policy and institutional resources and supervision. PT. Prima Lestari Investindo (Ramayana Mall) realization UKL was quite successful, realization UPL did not succeed. Factors that contribute to the realization are supervision and policy and institutional resources. PLTD Classification Realization UKL successful, realization UPL successful. Institutional, resource, policy and supervisory factors contributed equally to the realization of UKL-UPL.